2012
DOI: 10.1155/2012/532652
|View full text |Cite
|
Sign up to set email alerts
|

Pheromone Production, Attraction, and Interspecific Inhibition among Four Species ofIpsBark Beetles in the Southeastern USA

Abstract: Hindgut volatiles from attacking, unmated males ofIps avulsus, I. calligraphus, I. grandicollis, andI. piniwere analyzed by combined gas chromatography and mass spectrometry. Based on the quantitative identifications of hindguts and subsequent individual aerations, baits were formulated and a combined species-specific subtractive field bioassay was set up for the four bark beetle species. The bioassays were subtractive for the compounds identified in the hindgut analysis of each species, and volatiles identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(48 citation statements)
references
References 44 publications
2
35
1
Order By: Relevance
“…(Ð)-Ipsdienol did not perform anywhere near the level of (Ϯ)-ipsdienol. Our results are consistent with those of Kohnle et al (1994), Birgersson et al (1995), Strom et al (2003), and Miller et al (2005). There may be no need to use costly ipsdienol lures with high optical purity in a monitoring or detection program for I. avulsus.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…(Ð)-Ipsdienol did not perform anywhere near the level of (Ϯ)-ipsdienol. Our results are consistent with those of Kohnle et al (1994), Birgersson et al (1995), Strom et al (2003), and Miller et al (2005). There may be no need to use costly ipsdienol lures with high optical purity in a monitoring or detection program for I. avulsus.…”
Section: Discussionsupporting
confidence: 92%
“…In addition to potential differences in enantiomeric ratios of shared components, the southern Ips species have qualitative blend differences in pheromone blends. I. calligraphus uses ipsdienol and cis-verbenol, I. avulsus uses ipsdienol and lanierone, and I. grandicollis uses ipsenol alone Vité et al 1972Vité et al , 1976Birgersson et al 1995, Miller et al 2003, 2005.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary trials were conducted to determine the attractiveness of the full synthetic blend dissolved in heptane (Merck, Darmstadt, DE), with release rates between 3 to 100 ng min −1 of α-pinene within the blend with four replications to identify the optimum release rate for the test system. The blend was released by diffusion from a wick dispenser made out of a 2 ml glass vial with a pin hole in the centre of the cap through which a cotton wick encased in Teflon protruded into the air46. The wick dispenser allows for the release of all compounds in constant proportions throughout the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have attempted to identify speciÞc mechanisms of mate location among the southern Ips by using synthetic copies of pheromones (Vité and Renwick 1971;Renwick and Vité 1972;Hedden et al 1976;Vité et al 1976Vité et al , 1978Birgersson et al 1995;Strom et al 2003;Miller et al 2005). In general, these studies reported that the most attractive blend for the southern Ips involves one or more of ipsenol, ipsdienol, or cis-verbenol.…”
mentioning
confidence: 99%